Testosterone, cortisol and alpha-amylase levels during a handball match; analysis of dynamics and associations - Foretic, N.; Nikolovski, Z.; Peric, I.; Sekulic, D. (Research in Sports Medicine, 2020)
This study evaluated dynamics of testosterone, cortisol and alpha-amylase during a handball match in high-level male players. Ten male professional players (24.1 ± 3.1 years, 188.2 ± 6.4 cm, 94.6 ± 9.6 kg) were tested on salivary-testosterone, -cortisol and -alpha-amylase levels before (prematch), at halftime, and immediately after the game. Analysis of variance for repeated measurements (ANOVA) with consecutive post-hoc analyses and effect-size differences were calculated to identify differences between measurements. The associations among biomarkers were determined by Pearson`s product moment correlation (Pearson`s r). The ANOVA indicated significant differences in testosterone (F: 14.31, p < 0.01; significant post-hoc differences between prematch and remaining two measurements), and alpha-amylase (F: 9.78, p < 0.01; significant post-hoc differences between all measurements). Significant correlations were evidenced between: (i) alpha-amylase- and testosterone-changes during 1st halftime (Pearson`s r: 0.81, p < 0.01), and (ii) alpha-amylase- and cortisol-changes during 2nd halftime (Pearson`s r: 0.76, p < 0.05). The results indicated specific dynamics of biomarkers during the handball match, with significant increase in alpha-amylase during the entire match and significant increase in the testosterone level during the first half of the match. Further studies are needed to evaluate the associations between real-game performance and changes in hormonal responses.